Peranan UKM Sambal Jeruk Terhadap Peningkatan Pendapatan Masyarakat - Asyari, Akhmad; Fauzie, Marjan Azmu; Rasidi, Muhamad Ahyar (Lembaga Penelitian dan Pendidikan Mandala, 2022)
This study aims to determine the development of small and medium enterprises, the processes and constraints faced by small and medium enterprises in Parado Village, Bima Regency. This study uses a qualitative approach with a descriptive method with data collection techniques using interviews and documentation. The results of this study indicate that: (1) the development of Sambal Jeruk SMEs has increased in quantity and has a positive impact on people's income to become more prosperous, increase people's income as a source of additional income and directly create jobs and meet daily needs such as food, as well as other needs such as the health of their families and the need for their children's education. The obstacles in the process of making orange sauce are the procurement of materials for making orange sauce such as oranges, bottles, salt, chili and capital.